The association between caregivers' anxiety and sleep disturbances among preschool children in rural areas of China: The moderating effect of resilience. (December 2021) - Zhao, Tianming; Xuan, Kun; Liu, Haixia; Chen, Xin; Qu, Guangbo; Wu, Yile; Zhang, Jian; Sun, Yehuan
Highlights: In rural areas of China, about 89.4% of preschool children have potential sleep disturbances. Caregivers' anxiety (including parental anxiety and other relatives' anxiety) is associated with sleep disturbances of preschool children. Resilience of preschool children could attenuate the association between caregivers' anxiety and sleep disturbances of preschool children. In specific sleep domain of CSHQ, the moderating effect of resilience significantly existed in sleep duration and daytime sleepiness. Abstract: This study aimed to explore the association between caregivers' anxiety and sleep disturbances of preschool children aged from 3 to 6 years in rural areas of Anhui province, China. Besides, we also explored whether there is a mediated effect of resilience on this association. Caregivers of children from 26 kindergartens completed a structured questionnaire, the Children's Sleep Habits Questionnaire (CSHQ), Self-rating Anxiety Scale (SAS) and the Devereux Early Childhood Assessment for Preschoolers, Second Edition (DECA-P2). CSHQ, SAS and DECA-P2 were used to evaluate sleep disturbances among preschool children, the caregivers' anxiety, and the resilience of preschool children respectively. A total of 3, 802 questionnaires were distributed in our investigation, after checking for completeness, 166 invalid questionnaires were excluded and 3, 636 questionnaires were eventually included in our study. Binary logistic analysis was utilized to explore the potential relationship between caregivers' anxiety and sleep disturbances of children. Moderating effect of resilience was evaluated through calculating the percentage of change in odds ratios (OR) in the models with and without resilience. 10% or more of percentage change in OR was defined as a significant mediation effect. In our study, 89.4% of the preschool children aged from 3 to 6 years had potential sleep disturbances. In preschool children whose caregivers are their parents, the correlation between caregivers' anxiety and sleep disturbances of preschool children is statistically significant (OR = 10.168, 95 %CI:2.506–41.263). In preschool children whose caregivers aren't their parents, the correlation is also significant (OR = 2.405, 95 %CI:1.139–5.077). Furthermore, resilience could attenuate the association between caregivers' (including parents and other relatives) anxiety and sleep disturbances amongst preschool children. After adjusting resilience, the association between caregivers' anxiety and sleep disturbances of preschool children was attenuated and remained significant (OR for parents = 9.323, 95 %CI:2.295–37.875; OR for other caregivers = 2.232, 95 %CI:1.050–4.745). In specific sleep domain of CSHQ, the moderating effect of resilience significantly existed in sleep duration and daytime sleepiness. Our study indicated that caregivers' anxiety was associated with sleep disturbances among preschool children. High resilient children may be partly protected against the negative effect of caregivers' anxiety on their sleep quality. Future well-designed cohort studies are needed to further explore this topic in more details.